Supply Chain and Firm Performance with the Moderating Role of Leadership Dependency - Rahman Ambo Masse; Ali Halidin; M. Majdy Amiruddin; Kamaluddin Nurdin Marjuni (International Journal of Supply Chain Management, 2020)
The prime objective of the present study is to examine the role of supply chain leadership, supply chain fellowship and shared common values on the supply chain activities of the Islamic banks in Indonesia. The secondary objective of the ongoing study is also the examination of moderating role of supply chain leadership dependency among the links of supply chain leadership, supply chain fellowship, shared common values and supply chain activities of the Islamic banks in Indonesia. The questionnaire method has been adopted by the study to collect the data while smart-PLS has been executed for the analysis. The results indicated that supply chain leadership, supply chain fellowship and shared common values have a positive impact on the supply chain activities of the Islamic banks in Indonesia. The results also exposed that supply chain leadership dependency positively moderated among the links of supply chain fellowship and supply chain activities. These findings are suitable for the regulators along with further studies in terms of investigating, formulating strategies and policies on the supply chain activities of the banks.